Mitochondrial and nuclear intraspecific variation in the rusty blenny (Parablennius sanguinolentus, Blenniidae) - Pappalardo, Anna Maria (2017)
The genetic structure of Parablennius sanguinolentus from the northeastern Atlantic and Mediterranean was assessed using sequences from the mitochondrial control region (CR) and the first intron of the nuclear S7 ribosomal protein gene (S7). Our data show high genetic diversity for the central Mediterranean populations, contrasting with very low diversity in the Atlantic populations and in the westernmost Mediterranean population of Cabo de Gata. Both CR mismatch analysis and neutrality tests provide evidence of demographic and spatial expansion for the Atlantic and central Mediterranean populations. The significant correlation between genetic and geographic distances supported isolation- by-distance for the S7, but not for the CR, suggesting a complex scenario for the history of the rusty blenny in the Mediterranean Sea. The pattern of genetic structure displayed by P. sanguinolentus could be explained as the result of a post-glacial colonization of the Atlantic coast of Europe from the Mediterranean Sea.